California Takes the Lead on Data Privacy Law - Rothstein, Mark A. (The Hastings Center report, 2019)
In the early 1970s, Congress considered enacting comprehensive privacy legislation, but it was unable to do so. In 1974, it passed the Privacy Act, applicable only to information in the possession of the federal government. In the intervening years, other information privacy laws enacted by Congress, such as the Health Insurance Portability and Accountability Act, have been weak and sector specific. With the explosion of information technology and the growing concerns about an absence of effective federal privacy laws, the legal focus has shifted to the states. Signaling a new direction in state data privacy and consumer protection law, the California Consumer Privacy Act establishes important rights and protections for California residents with regard to the collection, use, disclosure, and sale of their personal information. The CCPA is certain to spur similar legislation and to affect national and international businesses that collect data from California's residents. Understanding the new law is important for all data-driven industries, including health care.